Correlation of functional and radioligand binding characteristics of GPER ligands confirming aldosterone as a GPER agonist - Qingming Ding; Jozef Chorazyczewski; Robert Gros; Harvey J. Motulsky; Lee E. Limbird; Ross D. Feldman (Wiley, 2022)
Abstract Aldosterone exerts some of its effects not by binding to mineralocorticoid receptors, but rather by acting via G protein‐coupled estrogen receptors (GPER). To determine if aldosterone binds directly to GPER, we studied the ability of aldosterone to compete for the binding of [3H] 2‐methoxyestradiol ([3H] 2‐ME), a high potency GPER‐selective agonist. We used GPER gene transfer to engineer Sf9‐cultured insect cells to express GPER. We chose insect cells to avoid interactions with any intrinsic mammalian receptors for aldosterone. [3H] 2‐ME binding was saturable and reversible to a high‐affinity population of receptors with Kd = 3.7 nM and Bmax = 2.2 pmol/mg. Consistent with agonist binding to G Protein‐coupled receptors, [3H] 2‐ME high‐affinity state binding was reduced in the presence of the hydrolysis‐resistant GTP analog, GppNHp. [3H] 2‐ME binding was competed for by the GPER agonist G1, the GPER antagonist G15, estradiol (E2), as well as aldosterone (Aldo). The order of potency for competing for [3H] 2‐ME binding, namely 2ME > Aldo > E2 ≥ G1, paralleled the orders of potency for inhibition of cell proliferation and inhibition of ERK phosphorylation by ligands acting at GPER. These data confirm the ability of aldosterone to interact with the GPER, consistent with the interpretation that aldosterone likely mediates its GPER‐dependent effects by direct binding to the GPER. Significance statement Despite the growing evidence for aldosterone's actions via G protein‐coupled estrogen receptors (GPER), there remains significant skepticism that aldosterone can directly interact with GPER. The current studies are the first to demonstrate directly that aldosterone indeed is capable of binding to the GPER and thus likely mediates its GPER‐dependent effects by direct binding to the receptor.